2021
DOI: 10.1002/jcla.23867
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative lipid profiles and new‐onset diabetes after transplantation in Chinese kidney transplant recipients: A retrospective cohort study

Abstract: Background This study investigated the association between the preoperative lipid profiles and new‐onset diabetes after transplantation (NODAT) in Chinese kidney transplant recipients (KTRs). Methods In this study, of 1140 KTRs registered between January 1993 and March 2018 in Zhongshan Hospital, Fudan University, 449 were enrolled. Clinical data, obtained through a chart review of the patient records in the medical record system, were evaluated, and NODAT was diagnosed based on the American Diabetes Associati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…However, previous research has indicated that the accumulation of excess cholesterol can lead to β-cell dysfunction, resulting in impaired glucose tolerance and compromised insulin secretion. Furthermore, deposition of cholesterol in the islets may contribute to increased aggregation of islet amyloid polypeptide and the formation of islet amyloid, further exacerbating β-cell dysfunction and impacting glucose regulation [ 23 26 , 56 ]. Therefore, it is plausible that the reduction in non-HDL-c/HDL-c ratio levels may have improved β-cell function, ultimately facilitating the reversal of IFG to normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research has indicated that the accumulation of excess cholesterol can lead to β-cell dysfunction, resulting in impaired glucose tolerance and compromised insulin secretion. Furthermore, deposition of cholesterol in the islets may contribute to increased aggregation of islet amyloid polypeptide and the formation of islet amyloid, further exacerbating β-cell dysfunction and impacting glucose regulation [ 23 26 , 56 ]. Therefore, it is plausible that the reduction in non-HDL-c/HDL-c ratio levels may have improved β-cell function, ultimately facilitating the reversal of IFG to normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an observational investigation has indicated that the non-HDL-c/HDL-c ratio outperforms other markers in predicting metabolic syndrome and insulin resistance [ 22 ]. Additionally, several recent studies have established a close association between the non-HDL-c/HDL-c ratio and the occurrence and progression of IFG and T2DM [ 23 26 ]. Moreover, a further study found that the non-HDL-c/HDL-c ratio serves as a superior marker for predicting diabetes risk compared to conventional lipid parameters in the general population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the association between lipids and T2D and the effectiveness of four lipid derivatives in predicting T2D risk [8][9][10][11][12]. However, the identification of the lipid derivative for predicting T2D risk in a clinical setting is still unclear.…”
Section: Comparisons With Other Studies and What Does The Current Wor...mentioning
confidence: 99%
“…High triglyceride (TG) and decreased high-density lipoprotein (HDL) are indicators of lipid metabolism disorders in T2D [7]. Furthermore, substantial evidence has shown [8][9][10][11][12] an association between lipid levels and T2D risk, and changes in lipid levels precede hyperglycemia [8,13]. In brief, an association was observed between alterations in lipid levels and the risk of developing T2D in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that excess cholesterol accumulation leads to β-cell dysfunction, thereby impairing glucose tolerance and affecting insulin secretion. In addition, islet cholesterol deposition may lead to increased islet amyloid polypeptide aggregation and increased islet amyloid formation, further deteriorating beta-cell function and affecting glucose homeostasis [9][10][11][12]. More importantly, they are also considered to be more predictive of CHD than conventional lipid parameters.…”
Section: Introductionmentioning
confidence: 99%